2000
DOI: 10.1038/77670
|View full text |Cite
|
Sign up to set email alerts
|

SLO-2, a K+ channel with an unusual Cl− dependence

Abstract: The gating of different potassium channels depends on many diverse factors. We now report a unique example of a K+ channel with a Cl - dependence. The slo-2 gene was cloned from Caenorhabditis elegans and is widely expressed in both neurons and muscles; it was highly abundant, as suggested by its high representation in the C. elegans EST database. SLO-2, like its paralogue, SLO-1, was also dependent on Ca 2+. We show by site-directed mutagenesis that its requirements for both Cl- and Ca2+ are synergistic and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
124
0

Year Published

2002
2002
2012
2012

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 111 publications
(128 citation statements)
references
References 40 publications
4
124
0
Order By: Relevance
“…In addition to the Ca 2ϩ -regulated Slo1 (Adelman et al, 1992;Butler et al, 1993) and the pH-regulated Slo3 (Schreiber et al, 1998), two additional homologs have been identified, Slo2.1 (Bhattacharjee et al, 2003), also termed Slick, and Slo2.2 (Joiner et al, 1998;Yuan et al, 2000Yuan et al, , 2003, also termed Slack. Slo2.2 subunits are regulated by both Na ϩ and Cl Ϫ (Yuan et al, 2003) and perhaps by Ca 2ϩ (Yuan et al, 2000), and Slo2.1 subunits, although less well characterized, also share sensitivity to Na ϩ and Cl Ϫ (Bhattacharjee et al, 2003). Thus, the hallmark of the Slo family of channels appears to be regulation by distinct cytosolic ligands.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the Ca 2ϩ -regulated Slo1 (Adelman et al, 1992;Butler et al, 1993) and the pH-regulated Slo3 (Schreiber et al, 1998), two additional homologs have been identified, Slo2.1 (Bhattacharjee et al, 2003), also termed Slick, and Slo2.2 (Joiner et al, 1998;Yuan et al, 2000Yuan et al, , 2003, also termed Slack. Slo2.2 subunits are regulated by both Na ϩ and Cl Ϫ (Yuan et al, 2003) and perhaps by Ca 2ϩ (Yuan et al, 2000), and Slo2.1 subunits, although less well characterized, also share sensitivity to Na ϩ and Cl Ϫ (Bhattacharjee et al, 2003). Thus, the hallmark of the Slo family of channels appears to be regulation by distinct cytosolic ligands.…”
Section: Discussionmentioning
confidence: 99%
“…1a. Two BK-like channels with somewhat smaller conductance than BK channels (100-200 pS) had either two conserved negative charges (mSlo3) (40,41) or one conserved negative charge (cSlo2) (42). MthK, a bacterial Ca 2ϩ -regulated K ϩ channel (31) with conductance of Ϸ100 pS at ϩ25 mV has two negative charges and one positive charge in the region equivalent to 321 and 324 of BK channels.…”
Section: Bk Channels Have a Ring Of Eight Negative Chargesmentioning
confidence: 99%
“…The gene coding for BK was called Slowpoke or Slo and, after the cloning and expression of Slo2 (Yuan et al, 2000;Yuan et al, 2003) and Slo3 (Schreiber et al, 1998), was renamed Slo1. In the case of Kv channels, the channelforming protein possesses six transmembrane domains (S1-S6) containing the pore-forming domain S5-P-S6 and an S4 voltage-sensing element.…”
Section: Sensing Elementsmentioning
confidence: 99%